Proses Berpikir Siswa Berkecerdasan Matematis Logis Dalam Menyelesaikan Masalah Matematis “Ill Structured Problems” - Siti Nurjanah; Erry Hidayanto; Swasono Rahardjo (Graduate School of Universitas Negeri Malang, 2019)
Abstract: Understanding the thinking process of students in mathematical problem solvingis very important for the teacher. Every student has different abilities in problems solving. Ill structured problems depend on the type of intelligence they have. This research uses descriptive qualitative research. The purpose of this study is to describe the thinking process of students with logical mathematical intelligence in solving limited mathematical information problems. The subject of this study consisted of one grade VIII junior high school student who had high logical mathematical intelligence. The results showed that the thinking process of students with logical mathematical intelligence in completing